Preoperative Systemic Therapy Versus Upfront Surgery in HER2-Positive Breast Cancer in the Real World - Yu, Xingfei; Wang, Chen; Zheng, Yabing; Miao, Beibei; Hu, Jiejie; Shao, Xiying; Sheng, Liming; Lin, Juan; Ding, Yuqin; Xuan, Haojun; Ding, Yingying; Gong, Lijie; et al. (Frontiers in Oncology, 2021)
Purpose: To compare survival in different strategies, preoperative systemic treatment versus upfront surgery, in HER2-positive early breast cancer patients in the real world. Methods: According to the actual upfront treatment, eligible patients from 2012 to 2015 were classified as preoperative systemic treatment or upfront surgery group prospectively. The primary endpoint is disease-free survival, the second endpoint is overall survival. All the outcomes were examined in the propensity score matching model and inverse probability of treatment weighting model. Results: Finally, 1067 patients (215 in the preoperative systemic treatment group, 852 in the upfront surgery group) were included in the analysis. In the propensity score matching model (matching at 1:1 ratio), the disease-free survival of the preoperative systemic treatment group was significantly higher than that of the upfront surgery group (hazard ratio, 0.57s2, 95%CI, 0.371~0.881, P, 0.012). In the inverse probability of treatment weighting model, there was no significant difference in disease-free survival between the two groups (hazard ratio, 0.946, 95%CI, 0.763~1.172, P, 0.609). For overall survival, there was no significant difference between the two groups. Conclusions: The HER2-positive patients accepted preoperative systemic treatment had better disease-free survival than those underwent upfront surgery by real-world statistic methods.